KEARIFAN LOKAL DAN NILAI MODERASI: Analisis Tokoh Punakawan dalam Budaya Pewayangan Jawa - Mukhlis, Ngatmin Abbas; Fathurrohman, Mukhlis; Mahmud, Amir (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2025)
This research aims to analyze the concept of moderation in Javanese puppetry represented through Punakawan characters, identify its actualization in contemporary contexts, and examine its theoretical and practical implications for developing moderation approaches based on local wisdom. Using library research methods with a qualitative-interpretive approach, this study analyzes various primary and secondary sources related to Punakawan and the concept of moderation. The results show that moderation in Punakawan characters is represented in three dimensions: philosophical through spiritual-material balance, social through roles as bridges between groups, and praxis through humorous approaches in social criticism. The actualization of Punakawan moderation values can be applied to address socio-political polarization, socio-economic disparities, and cultural identity crises. This research contributes to developing moderation theory based on local wisdom and provides practical guidance for character education programs, conflict resolution, and moderate leadership. The novelty of this research lies in its integrative approach that connects Punakawan local wisdom with contemporary moderation theory, producing a transformative framework that is adaptive to today’s social challenges.